Food chemistry and biochemistry of enzymatic browning - Murata, Masatsune (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2022)
Food chemistry and biochemistry of enzymatic browning are reviewed with a focus on the author's research and recent information. Enzymatic browning is categorized into two types, immediate and delayed, according to the time required for browning. Apple browning has been extensively examined as an example of the former. The enzyme polyphenol oxidase (PPO) and its substrate polyphenols are separated into plastids and vacuoles, respectively, in cells. Disruption of this compartmentation by cutting, crushing, wounding, and physiological disorders allows interaction of the enzyme and substrate, and the reaction starts to turn brown. For the immediate type of enzymatic browning, regulation of oxidative polymerization of phenolic compounds by PPO is essential to inhibit browning. Browning of cut lettuce and mung bean sprouts are described here as the delayed type, in which phenylalanine ammonia-lyase (PAL) is induced during storage and phenolic compounds are synthesized de novo. The formed phenolic compounds are successively oxidized by PPO to turn brown. Regulation of PAL induction is crucial to inhibit this type of browning. Treatments with mild heat shock and cinnamaldehyde are described here as physical and chemical methods, respectively, to repress PAL induction and browning.